Association of microRNA-33a Molecular Signature with Non-Small Cell Lung Cancer Diagnosis and Prognosis after Chemotherapy. - Li-Kun Hou; Yu-Shui Ma; Yang Han; Gai-Xia Lu; Pei Luo; Zheng-Yan Chang; Ru-Ting Xie; Hui-Qiong Yang; Li Chai; Ming-Xiang Cai; Ting-Miao Wu; Fei Yu; et al. (PLoS ONE)
Objective This study aims to explore the expression pattern and prognostic significance of miR-33a in non-small cell lung cancer (NSCLC) treated with adjuvant chemotherapy. Methods MiR-33aexpression in NSCLC was analyzed in silico using the GEO database and was subsequently confirmed by quantitative RT-PCR in 147 NSCLC biopsies. Among these, 32 of these biopsies were paired with adjacent non-neoplastic tissues. The survival analysis of NSCLC by Kaplan-Meier estimates was stratified based on miR-33a expression. In addition, multivariate survival analysis in corresponding groups of NSCLC patients was conducted by Cox proportional hazards regression model. Results The in silico analysis of miR-33a expression in NSCLC resulted to its down-regulation in different tumor types. The expression level of miR-33a was lower in each grade of NSCLC tumor biopsies than in normal lung tissues. Univariate and multivariate survival analysis further established that low miR-33a expression was an important risk factor for overall survival and disease free survival in NSCLC patients. Conclusion Our study implied that miR-33a expression levels may have an essential role in NSCLC progression, and could act as a specific and sensitive biomarker for NSCLC patients who have undergone adjuvant chemotherapy.